Geopolitical risks and natural resources rents: Evidence from BRICs countries - Phuc, Doan Ngoc (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to examine the impact of geopolitical risks on natural resource rents in BRICS countries. The current study uses wavelet analysis to examine the relationship between geopolitical risks and natural resource rents in BRICS (China, India, Russia, Brazil, and South Africa) economies over time-frequency space from 1990 to 2020. The wavelet-based analysis results reveal that the co-movement between natural resource rents and geopolitical instability in BRICS countries appears to be changing simultaneously over different time periods and different frequencies. More importantly, our empirical results highlight that these geopolitical risks negatively impact natural resource rents at medium and low frequencies in China, India, Russia, and Brazil, while geopolitical risks positively impact natural resource rents in South Africa over the sample period. From the research results, some policy implications related to sustainable development or conservation of natural resources for future generations are suggested.